A built environment response to the rising costs of dementia. Issue 2 (1st August 2016) - Pantzartzis, Efthimia; Price, Andrew D. F.; Pascale, Federica
Abstract : Purpose: This paper identifies costs related to dementia care provision and explores how purposeful built environment investments can help control these costs and improve Quality of Life and clinical outcomes. Design/methodology/approach: This research adopts a multi-method approach where the findings of a literature review drove the analysis of data obtained from the 115 pilot projects funded by the Department of Health England's National Dementia Capital Investment Programme. Findings: Under the UK government's new productivity challenge, it is fundamental to identify actions that provide Value for Money in order to prioritise policy and practice. This paper identifies healthcare spaces (e.g. bathroom) where the impact of the built environment on healthcare costs are most evident, and building elements (e.g. lighting) to which these costs can be directly associated. The paper advocates the development of evidence and decision support tools capable of: linking built environment interventions to the healthcare costs; and helping the health and social care sectors to develop effective and efficient capital investment strategies. Research limitations/implications: Further work needs to develop more systematic ways of rationalising pro-active and timely built environment interventions capable of mitigating dementia (and elderly) care cost escalation. Originality/value: This research takes an innovative view on capital investment for care environments and suggests that appropriate built environment interventions can have a profound impact on costs associated with dementia care provision.